A simple terpyridine–cobalt(II) complex sensitized by connective mpg–C3N4 for improved CO2 photoreduction. (August 2022) - Chen, Longxin; Wu, Yunying; Hu, Yufang; Chao, Duobin
Abstract: A noble metal–free hybrid photocatalysts (Cotpy@mpg–C3 N4 ) composed of mesoporous carbon nitride (mpg–C3 N4 ) and a simple molecular terpyridine–Co(II) complex (Co(ptpy)Cl2 ) has been synthesized for CO2 photoreduction. The hybrid photocatalyst exhibited high and durable CO formation (3.41 × 10 4 μmol g –1 ) after 48 h of visible light irradiation, which is much better than corresponding separated system without a covalent connection. The introduction of Co(ptpy)Cl2 to mpg–C3 N4 via a covalent amido bond in Cotpy@mpg–C3 N4 improved the reducing ability of conduction bond (–1.58 V vs. SCE) and CO2 adsorption capacity (3.23 mmol g –1 ). Further mechanistic studies revealed that the efficient cooperation between light–absorbing mpg–C3 N4 and catalytic site Co(ptpy)Cl2 was crucial and facilitated electron transfer and charge separation during photocatalysis. This work highlights the synergistic effect of constituent components in the hybrid photocatalyst for CO2 photoreduction. Highlights: A noble metal-free hybrid photocatalyst was prepared for efficient CO2 reduction. The covalent connection facilitated electron transfer during CO2 photoreduction. The hybrid could be recycled to generate 3.41 × 10 4 μmol g –1 CO. Mechanistic studies revealed the synergistic effect for improving CO2 reduction.